CORRUPTION'S EFFECT ON FOREIGN DIRECT INVESTMENT – THE CASE OF MONTENEGRO - Elvira Pupović (Economic Review)
All investments and asset classes have different levels of risks and expected returns. For example, low risk investments such as cash generally provide a lower return than high risk investments over the long term, but are unlikely to lead to a capital loss. High risk investments generally offer the potential of a higher return over the long term, but there is a higher probability that high risk investments will be more volatile in the short term (leading to capital loss if funds are withdrawn in the short term). This study introduces a new perspective on the role of corruption in investment growth and provides quantitative estimates of the impact of corruption on the investment inflows. Motivated by these issues, the main objective of this article is to empirically reexamine the effects of corruption on foreign direct investment (FDI) inflows by incorporating a further link between corruption and investment inflows as new understanding investment concepts. Using data from Transparency International report, World Bank and National Banking Statistical data, it is manifested in a cross sectional setting that corruption has a negative and significant impact on the foreign direct investment inflows. There are a number of risks to be considered such as investment market risk, credit risk or interest rate risk, but the new model of eliminated unexpected risk involved managing corruption's effect on investments. Because of the need that assessing risk and potential investment returns should be in the context of goals and the time that we have to achieve our objectives, we have to immediately consider the linkage between corruption and investment inflows and to teach how to manage this phenomenon like an old risk of a new model.